MODERN STATE OF THE PROBLEM OF DIAGNOSIS AND SURGICAL TREATMENT OF HEART ECHINOCOCCOSIS (Yangi O'zbekiston taraqqiyotida tadqiqotlarni o'rni va rivojlanish omillari, 2024)
Echinococcosis of the heart is rare, accounting for only up to 2.0% of all localizations of this zooanthroponosis [1, 4, 6, 8, 10, 11]. A small number of works on cardiac echinococcosis surgery draws attention [1-3, 10]. The paucity of publications and clinical observations on diagnosis and surgical treatment indicates a lack of awareness of clinicians about diagnostic features and methods of surgical treatment. However, in endemic areas there is a rather "high" frequency of patients with cardiac echinococcosis who need surgical treatment.